Research on vacuum properties of CuCrZr UHV flanges for the Hefei Advanced Light Facility. (January 2022) - Bian, Baoyuan; Wang, Sihui; Wei, Wei; Hong, Yuanzhi; Fan, Le; Zhu, Bangle; Ge, Xiaoqin; Wang, Yigang; Fang, Jianwei; Zhang, Wenli; Shang, Lei; Wang, Yong
Abstract: Hefei Advanced Light Facility (HALF), one of the Diffraction-Limited Storage Rings (DLSR), requires low-impedance flanges to be welded with Oxygen-free with Ag (OFS) vacuum chamber. In this paper, CuCrZr alloy as flange material and spring energized metal C-ring sealing structure are proposed. Two types of CuCrZr flanges have been designed, which are chain clamp and bolted flange, respectively. Chain clamp flanges are planed for compact areas, due to its small axial dimension. Bolted flanges with better positioning ability are designed to place in sections without space limitation. A series of leak rate and outgassing rate measurements were performed, and force and finite element analyses were carried out. Leak rates of both two flanges are lower than 5 × 10 − 13 P a m 3 s − 1 after 10 times seal-changing tests and 15 times same-seal bakeout cycles. Required fastening torques of chain clamp and bolted flange are 5–7 N m and 3–5 N m, respectively, in order to achieve sealing. The outgassing rate of CuCrZr is about an order of magnitude less than that of stainless steel after bakeout to 250 °C. The simulation results indicate that stress on the CuCrZr flange is far lower than metal C-ring due to the large deformation of the seal. Highlights: CuCrZr alloy is chosen as flange material, and a sealing structure using spring energized metal C-ring is proposed. Chain clamp and bolted flange are designed for compact areas and areas without space limitation, respectively. The leak rates of two types of CuCrZr flanges are lower than 5 × 10 − 13 P a m 3 s − 1 . The required fastening torques of the CuCrZr chain clamp and bolted flange are 5–7 N m and 3–5 N m, respectively. The linear load calculation by fastening torque and finite element method is studied.